COMMUNICATIVE COMPETENCE OF LOCAL SELF-GOVERNMENT OFFICIALS IN THE CONTEXT OF DIGITAL TRANSFORMATION AND WARTIME CHALLENGES (Coordinates of Public Administration, 2026)
The article conceptualises the communicative competence of local self-government officials as a multidimensional professional capacity that combines the ability to ensure meaningful, ethically balanced, legally compliant, and technologically mediated interaction with residents of territorial communities, public authorities, civil society institutions, media actors, volunteer organisations, and digital service ecosystems. It is substantiated that, under conditions of digital transformation, communication within local government is no longer limited to purely informational and explanatory functions, but increasingly acquires the characteristics of a continuous managerial process aimed at strengthening public trust, ensuring citizen participation, coordinating social interests, responding promptly to community needs, and enhancing the transparency and legitimacy of managerial decisions. It is demonstrated that digitalisation transforms not only the technological infrastructure of communication, but also the very logic of public-authority interaction: instead of predominantly one-way information delivery, a multichannel model of communication is emerging, based on feedback mechanisms, data openness, personalised access to public services, and a citizen-centred approach to governance. The study establishes that, under martial law, the communicative competence of local self-government officials acquires strategic security-related, crisis-management, and socially integrative significance, since its effectiveness directly influences the timeliness of public informing, the ability to prevent panic and social destabilisation, counter disinformation, maintain community psychological resilience, and ensure the continuity of managerial interaction under conditions of threat and uncertainty. The principal structural components of communicative competence are identified as follows: legal-regulatory, digital-communication, crisis-communication, ethical-psychological, information-analytical, and coordination-partnership components. A conceptual framework for the development of communicative competence is proposed through the modernisation of professional training for local self-government officials, strengthening digital and media literacy, developing competencies in crisis public dialogue, communication risk management.